Biomolecules & therapeutics - Hanʼguk Ŭnyong Yangmul Hakhoe (Korean Society of Applied Pharmacology, 2008)
Biomolecules & Therapeutics (Biomolecules & Therapeutics) (Print ISSN 1976-9148, Online ISSN 2005-4483) is an international, peer-reviewed, open access journal that covers pharmacological and toxicological fields related to bioactive molecules and therapeutics. It was launched in 1993 as "The Journal of Applied Pharmacology (ISSN 1225-6110)", and renamed "Biomolecules & Therapeutics" (Biomol Ther: abbreviated form) in 2008 (Volume 16, No. 1). It is published bimonthly in January, March, May, July, September and November. All manuscripts should be creative, informative, and contribute to the development of new drugs. Articles in the following categories are published: review articles and research articles.
Keywords: Biomolecules : Periodicals; Pharmacology : Periodicals; Pharmacology : methods; Drug Therapy; Biomolecules